2016
DOI: 10.1093/jtm/taw067
|View full text |Cite
|
Sign up to set email alerts
|

Cervical artery dissection at high altitude: an overview of two patients

Abstract: While altitude illness is common in the Himalayas, conditions unrelated to altitude illness also occur. High altitude cerebral oedema HACE is a global phenomenon of gradual onset affecting both cerebral hemispheres. We outline two cases of cervical artery dissection presenting with sudden onset of focal neurological symptoms at high altitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A recent report described two mountain climbers who developed acute onset of neck pain with symptoms similar to our patients, and their subsequent workup revealed spontaneous carotid artery dissection. 6 Although high altitude or mountain travel is not a known risk for carotid artery dissection, studies have identified altered cerebral blood flow dynamics at high altitude and endothelial dysfunction in response to hypoxia. 7 We postulate that the altered cerebral blood flow triggered by the high altitude with resultant endothelial dysfunction may have played a role in the development of carotidynia in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report described two mountain climbers who developed acute onset of neck pain with symptoms similar to our patients, and their subsequent workup revealed spontaneous carotid artery dissection. 6 Although high altitude or mountain travel is not a known risk for carotid artery dissection, studies have identified altered cerebral blood flow dynamics at high altitude and endothelial dysfunction in response to hypoxia. 7 We postulate that the altered cerebral blood flow triggered by the high altitude with resultant endothelial dysfunction may have played a role in the development of carotidynia in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several investigators suggested a potential impact of high altitude exposure on preexisting neurological conditions, and some of these disturbances falling outside the umbrella of altitude sickness have been documented in both case reports and reviews. These abnormalities included: migraine and other headaches, epileptic seizures, MS, permanent/transient ischemia of the brain, intracranial hemorrhage and vascular malformations, occlusive cerebral artery disease, cerebral venous thrombosis, intracranial space-occupying lesions, dementia, extrapyramidal disorders [154], cervical artery dissection, nystagmus, third and fifth cranial nerve palsies, eyelid ptosis, nystagmus [155], sixth nerve palsy, epilepsy [156], various ocular disturbances [157], retinopathy in otherwise healthy individuals [158], visual blurring, tinnitus, dysarthria, speech arrest, facial dysesthesia, generalized seizure, right-sided hemiparesis, ataxia, dizziness [159], and even meningioma [160]. Moreover, there was also reported a positive family history on epileptic disorders in father, brother, and daughter of the high altitude patient who had no preceding symptoms of acute mountain sickness [156], and a personal and familial vascular history in a 34-year old women with neurological symptoms [159].…”
Section: A Possible Association Between High Altitude Climbing Freque...mentioning
confidence: 99%